The Promise: Communist Organizing in the Needle Trades, the Dressmakers' Campaign, 1928-1937 - Steedman, Mercedes (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1994)
This paper deals with the Needle Trades Industrial Union (NITU) organization drive in the garment industry of the cities of Montréal, Toronto, and Winnipeg. I argue that the relative success of this branch of the Workers Unity League (WUL) in unionizing the female workforce originates in part from the union's internal representation structure. Women's work was isolated from men's by the sharp gender division of work, which characterized the garment trade. A union structure adopted to overcome this division of work, one based on the place of work (and not on the industrial branch) favoured women's participation to unionism.